LA NEGOCIACIÓN COLECTIVA EN EL PRIMER GOBIERNO DE IZQUIERDA DEL URUGUAY. - Pucci, Francisco; Nión, Soledad; Ciapessoni, Fiorella (Latin American Research Review, 2014)
The article discusses the collective bargaining reform carried out by the leftist government of Uruguay from 2005 to 2009, with a focus on the history of labor relations in the country. A historical overview of the labor movement in Uruguay is presented, focusing on the relationship between labor unions and political parties. Subjects discussed include the welfare doctrine known as battlismo established in the beginning of the 20th century by former president José Batlle y Ordóñez, the neoliberal policies implemented in the country during the 1990s, and an analysis of the labor laws enacted in 2009.